PENDIDIKAN ISLAM MULTIKULTURAL PEMIKIRAN NURCHOLISH MADJID - Akh Rosyidi (LPPM STIT Miftahul Ulum Bangkalan, 2019)
Abstract: Indonesia is a country known by its plurality consisting of several religions, diverse languages and cultures. This is the main attraction of various groups even from abroad to study it, although sometimes it causes various controversies. Multicultural Islamic education is a place to introduce Indonesia's plurality because education is considered the most ideal in its application. This article is a reflection of Nurcholish Madjid's thoughts on a very pluralistic, liberal and multicultural multicultural Islamic education. Keywords: multicultural Islamic education, nurcholish madjid Abstrak: Indonesia merupakan negara yang dikenal dengan kemajemukanya (plural) terdiri dari beberapa agama, beragam bahasa dan budaya. Hal tersebut menjadi daya tarik tersendiri dari berbagai kalangan bahkan dari kalangan luar negeri untuk mengkajinya, walaupun terkadang menimbulkan kontroversi. Pendidikan Islam multikultural merupakan wadah untuk mengenalkan kemajemukan Indonesia karena pendidikan dianggap paling ideal dalam penerapannya. Artikel ini menelalah pemikiran Nurcholish Madjid tentang pendidikan Islam multikultural yang sangat plural, liberal dan multikultur yang kontroversial. Katakunci: pendidikan islam multikultural, nurcholish madjid